Vaccination and treatment of influenza: achievements and challenges - N. I. Briko; V. V. Nikiforov; T. G. Suranova; N. A. Polezhaeva; T. S. Saltykova (Лечащий Врач)
Influenza is of great socio-economic importance due to the widespread prevalence and high mortality, especially among patients at risk. Vaccination is important in reducing the incidence and mortality from influenza. The article describes the indications for vaccination, risk groups, features of modern vaccines. The article presents recommendations for the treatment of various forms of influenza.